ANALISISIS KRIMINOLOGI KEJAHATAN KEKERASAN TERHADAP ORANG DAN BARANG DALAM LINGKUNGAN MASYARAKAT - Suslianto, Suslianto (At-Tanwir Law Review, 2025)
This study aims to understand crimes of violence against people and property in the community using criminological studies or research. This study is a sociological/non-doctrinal legal study that involves direct observation in the field and analysis using criminological theory. The results of this study reveal, first, that the factors contributing to violent crimes against people and property within a community include internal and external factors, as well as efforts to address such crimes, which encompass preventive and repressive measures.